Green Banking, ESG Performance, and Profitability on Bank Credit Risk: The Moderating Role of Asset Quality Using a Fuzzy Structural Risk Approach - Wafi Akhlaqil Karimah; Andam Dewi Syarif (Dinasti Publisher, 2026)
This study examines the effect of green banking, environmental social governance performance, and profitability on bank credit risk, with asset quality acting as a moderating variable. The research object consists of Indonesian conventional commercial banks classified as KBMI 3 and KBMI 4 during 2020–2024. The objective is to analyze whether sustainability integration reduces structural default vulnerability and how credit discipline conditions this relationship. The study applies panel data regression and moderated regression analysis using the Fuzzy Structural Risk of Default as a structural credit risk proxy. The results show that green banking is associated with higher short-term credit risk due to transition-related frictions. Environmental social governance performance significantly reduces credit risk, while profitability does not directly influence risk but strengthens stability when asset quality is strong. Asset quality functions both as a determinant and as a conditioning mechanism in sustainability–risk dynamics. The findings indicate that sustainable banking resilience depends on disciplined credit portfolio management during sustainability transition phases in emerging financial systems.